2018
DOI: 10.1021/acs.analchem.8b03810
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metal Ion Sensing by an Antipyrine Derivative in Aqueous and β-Cyclodextrin Media: Selectivity Tuning by β-Cyclodextrin

Abstract: β-Cyclodextrin (β-CD) is a nontoxic cyclic oligosachcharide that can encapsulate all or part of organic molecules of appropriate size and specific shape through noncovalent interaction. Herein, we report the influence of β-CD complex formation of an antipyrine derivative on its metal ion sensing behavior. In aqueous solution, the antipyrine shows a turn-on fluorescence sensing of vanadyl ion, and in cyclodextrin medium it senses aluminum ion. The compound shows an unusual fluorescence quenching on binding with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(9 citation statements)
references
References 47 publications
(66 reference statements)
1
7
0
Order By: Relevance
“…In recent times, the design of sensors (ions or small molecules) and their application in live cells for the detection of ions/molecules have received active interest from chemistry, physics, chemical engineering, electrical and electronic engineering, and many other branches. On considering the social and biological importance of Al­(III), some examples of fluorescent sensors have been reported for Al 3+ detection with the Schiff base scaffold of 4-aminoantipyrine derivatives, rhodamine B ligands, coumarinyl derivatives, benzophenone, chromone, diphenyl pyrrol derivatives, pyrazoles, quinolones, fluorenes, benzimidazoles, and so forth. Besides, a limited number of sensors exhibit aggregation-induced emission (AIE), and their emissivity, in some cases, has been influenced by Al 3+ ions .…”
Section: Introductionmentioning
confidence: 99%
“…In recent times, the design of sensors (ions or small molecules) and their application in live cells for the detection of ions/molecules have received active interest from chemistry, physics, chemical engineering, electrical and electronic engineering, and many other branches. On considering the social and biological importance of Al­(III), some examples of fluorescent sensors have been reported for Al 3+ detection with the Schiff base scaffold of 4-aminoantipyrine derivatives, rhodamine B ligands, coumarinyl derivatives, benzophenone, chromone, diphenyl pyrrol derivatives, pyrazoles, quinolones, fluorenes, benzimidazoles, and so forth. Besides, a limited number of sensors exhibit aggregation-induced emission (AIE), and their emissivity, in some cases, has been influenced by Al 3+ ions .…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that the formation of intermolecular hydrogen bond was conducive to the complexation between host and guest. [20] The carbonyl oxygen atoms of 1,8-naphthalimide and the 3-OH groups of the ring provided condition for the formation of hydrogen bonds, which was verified by the optimization results of Gaussian calculations (Figure S5). In addition, 1 H NMR titration experiment was operated by fixing LDs-NPAd2 (2 mM) and M-β-CD with different molar ratios (1 : 0, 1 : 2) to investigate the host-guest interaction (Figure S6).…”
Section: Development and Application In Fluorescent Makersmentioning
confidence: 55%
“…Recently, the importance of designing new molecular systems that facilitate the participation of heterocyclic nitrogen as ionophores for heavy metal ion recognition has been discussed ( Nagarajan et al, 2021 ). These designs can be associated with changes in the scaffold of the N -heterocyclic molecule which, using supramolecular host-guest systems, could act as a differential metal ion sensing ( Xu et al, 2010 ; Selvan et al, 2018 ), or in a synergetic binding mode ( Xu et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%